A critical analysis of the new design of the Barasoain church of Malolos as to its restoration - Dorupa, Mary Kristine Andres; Mayo, Adelaida Villaraza (1998.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Church architecture -- Conservation and restoration; Barasoain church (Malolos, Bulacan)